Handbook of chronic kidney disease management - Daugirdas, John T. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"It was an enormous privilege and an intellectual feast to interact with the eminent contributors to this Handbook who somehow managed to find time in their busy schedules to distill for us their knowledge and expertise regarding all aspects of diagnosing, treating, and preventing progression of CKD. It was our goal to develop a book that would be useful across the world, and special effort was made to recruit authors from various parts of the globe to better reflect the range of practices and problems encountered in different countries. Strict attention was paid to referencing not only U.S. guidelines, but also those in the United Kingdom, Europe, Canada, and Australia, and to express laboratory values using both metric and SI units"--Provided by publisher